2018
DOI: 10.3389/fnins.2018.00934
|View full text |Cite
|
Sign up to set email alerts
|

Orexin Depolarizes Central Amygdala Neurons via Orexin Receptor 1, Phospholipase C and Sodium-Calcium Exchanger and Modulates Conditioned Fear

Abstract: Orexins (OX), also known as hypocretins, are excitatory neuropeptides with well-described roles in regulation of wakefulness, arousal, energy homeostasis, and anxiety. An additional and recently recognized role of OX is modulation of fear responses. We studied the OX neurons of the perifornical hypothalamus (PeF) which send projections to the amygdala, a region critical in fear learning and fear expression. Within the amygdala, the highest density of OX-positive fibers was detected in the central nucleus (CeA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 57 publications
(100 reference statements)
1
22
0
Order By: Relevance
“…Central administration of orexin A strongly activated CeA neurons (Sakamoto et al, 2004) and CeA neurons were depolarized by orexin A and B (Bisetti et al, 2006;Dustrude et al, 2018).…”
Section: Orexin/hypocretinmentioning
confidence: 98%
See 1 more Smart Citation
“…Central administration of orexin A strongly activated CeA neurons (Sakamoto et al, 2004) and CeA neurons were depolarized by orexin A and B (Bisetti et al, 2006;Dustrude et al, 2018).…”
Section: Orexin/hypocretinmentioning
confidence: 98%
“…Orexins exert their excitatory actions through two types of receptors (OX 1 and OX 2 ,), with orexin A binding both OX 1 and OX 2 and orexin B showing much greater affinity for OX 2 . Orexin fiber and receptor expression is relatively dense within the amygdala (Ch'ng & Lawrence 2015; Marcus et al, 2001;Peyron et al, 1998), with greater innervation observed in the CeA over the adjacent LA and BLA nuclei (Dustrude et al, 2018;Peyron et al, 1998).…”
Section: Orexin/hypocretinmentioning
confidence: 99%
“…In this way, serotonin keeps GABAergic neuronal activity in check. Orexin can also excite inhibitory interneurons in the CeA (Dustrude et al, 2018; Hasegawa et al, 2017). GABAergic hyperactivity once triggered, could successively send overwhelming inhibitory inputs into the brainstem and cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Orexin-mediated Ca 2Ï© influx and release are also observed in neurons (28,35). Two different mechanisms, Ca 2Ï© influx via Ca 2Ï© channels and PLC-dependent Ca 2Ï© release, are associated with orexininduced elevation of intracellular Ca 2Ï© (13,33,34,39,68). The L-type Ca 2Ï© channel is involved in orexin-induced functional regulation of many neurons (34,39,64).…”
Section: Discussionmentioning
confidence: 99%